How to solve for x?

(x/(x+1))+ ((2x-2)/x) = -1/(x+1)

can someone show it step by step so i can understand it? Thanks!

1 answer

(x/(x+1))+ ((2x-2)/x) = -1/(x+1)
((2x-2)/x) = -1/(x+1) -x/(x+1)
((2x-2)/x) = (-1-x)/(x+1)
((2x-2)/x) = -(x+1)/(x+1)
((2x-2)/x) = -1
2x-2 = -x
2x+x = 2
3x = 2
x = 2/3
Similar Questions
  1. Fill in the spaces to solve each step of the problem 1/4(x+3)=5.(2 points)Step 1: (?)1/4(x+3)=5(?). Step 2: x+3=? . Step 3:
    1. answers icon 1 answer
  2. Fill in the spaces to solve each step of the problem 14(x+3)=5 .(2 points)Step 1: (?)14(x+3)=5(?). Step 2: x+3= ? .Step 3:
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 11 answers
more similar questions